Badger vs. beaver patterns in Romanian student life during the pandemic. A two-wave longitudinal approach - Nadolu, Bogdan; Petrescu, Magdalena (Frontiers in Education, 2022)
We have already experienced almost two years of Covid-19 pandemic related problems, stress and negative feelings. All over the world, various restrictions have been imposed to reduce the spread of the virus. A particular social category directly affected by the Covid-19 restrictions is that of students. In Romania, classes have been held online from March 2020 until April 2022 for a large part of the higher education system. How have students been affected by these semesters of online classes? This paper sets out to answer this research question on the basis of two sociological surveys, applied online in May 2020 (N=518) and in May 2021 (N=206). Its main finding is that there are two different patterns students employ in order to cope with the limitations imposed by the pandemic restrictions: the badger approach, in which they take refuge in leisure activities, and the beaver approach, involving more dynamic and sustainable behaviors.